2012
DOI: 10.1111/j.1755-3768.2012.02479.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual effect of prostaglandins on isolated intraocular porcine ciliary arteries

Abstract: ABSTRACT.Purpose: Prostaglandin analogues are used to reduce the intraocular pressure (IOP) in glaucoma, but also affect the tone of the arteries supplying the ciliary body. Previously, the effect of prostaglandins has been studied on the extraocular ciliary arteries, whereas the effect on intraocular ciliary arteries has not been studied in detail. Methods: Intraocular long posterior porcine ciliary arteries were isolated and mounted in a myograph system for isometric tension recording, and the effects of PGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
2
9
0
1
Order By: Relevance
“…A similar reduction of relaxation was observed in the presence of the EP 1 receptor antagonist SC 19220 which suggests that the effect had been mediated by prostaglandin E or other prostaglandins acting on this receptor in the vascular wall. Although a study has shown that prostaglandin E may elicit constriction of retinal arterioles [27], the present findings are consistent with several previous studies using the same model on both retinal and ciliary porcine arterioles [5,28,29]. Since ATP-γS-induced relaxation was unaffected by ibuprofen and EP 1 receptor antagonism, it is likely that the effect had been mediated by a degradation product from ATP.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A similar reduction of relaxation was observed in the presence of the EP 1 receptor antagonist SC 19220 which suggests that the effect had been mediated by prostaglandin E or other prostaglandins acting on this receptor in the vascular wall. Although a study has shown that prostaglandin E may elicit constriction of retinal arterioles [27], the present findings are consistent with several previous studies using the same model on both retinal and ciliary porcine arterioles [5,28,29]. Since ATP-γS-induced relaxation was unaffected by ibuprofen and EP 1 receptor antagonism, it is likely that the effect had been mediated by a degradation product from ATP.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, the presence of dual effects of purines on vascular tone with opposite responses at different concentrations and after different time lags [13,24] is supported by a previous study where adenosine was found to contract retinal arterioles at intermediate concentrations mediated by the A 1 and A 3 receptors and relaxation at high concentrations mediated by the A 2A and A 2B receptors [33]. The findings supplement previous studies, which showed that hypoxia-induced relaxation of porcine retinal arterioles and ciliary arteries is mediated by the EP 4 receptor [28,29] and thus adds to our understanding of the complexity of prostaglandin-induced tone regulation in retinal arterioles.…”
Section: Discussionsupporting
confidence: 80%
“…The observed effect could not be shown in a study based on a smaller number of observations, 22 but may be due to the fact that the unspecific COX-inhibitor diclofenac had antagonized the synthesis of several prostaglandin with opposite effects as shown in in vitro experiments. 23,24 This points to the need for studying the involvement of individual prostaglandins on pressure autoregulation of retinal arterioles.…”
Section: Figurementioning
confidence: 98%
“…Cette prostaglandine peut activer un ou plusieurs de ses propres récep-teurs (EP1, EP2, EP3 et EP4) de manière dose dépendante (Fig. 2) [39]. L'interaction avec ses différents récepteurs permet l'induction de signaux intracellulaires différents.…”
Section: Acide Arachidonique Et Formation D'adipocytes Blancsunclassified